JOINT HANDLING OF CORRUPTION CRIMINAL ACTS BETWEEN LAW ENFORCEMENT OFFICERS (POLICE-PROSECUTOR-KPK) AS SEEN FROM THE THEORY OF INTEGRATIVE LEGAL - T Subarsyah; Dedy Hernawan; Nawawi Pomolango (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Law enforcement efforts​ to uncover corruption crimes is not limited to convicting or imprisoning the perpetrators , but also involves recovering state losses by returning the assets and property they have misappropriated . This law enforcement effort is supported by the Draft Law on Asset Confiscation (Asset Confiscation Bill). This approach aligns with integrative legal theory , which emphasizes that multiple law enforcement agencies must collaborate in addressing corruption crimes . There is a legal basis for the cooperation between the Indonesian National Police, the Attorney General's Office, and the Corruption Eradication Commission (KPK) in handling corruption cases . In practice , however , there are still overlapping authorities and legal gaps arising from regulations , policies , or other statutory provisions , which can potentially lead to conflicts , deficiencies , or inefficiencies in tracing corruption cases . Therefore , this study aims to analyze the joint handling of corruption cases by law enforcement agencies in Indonesia, namely POLRI, the Attorney General's Office, and KPK, in the enforcement of anti -corruption laws . This study aims to analyze the joint handling of corruption cases by POLRI, the Attorney General's Office, and KPK in enforcing anti -corruption laws in Indonesia. Findings indicate that this collaboration is built on a solid legal framework and seeks to ensure law enforcement that is transparent , professional , and integrity-driven . In practice , several challenges remain , including overlapping authorities , weak coordination , sectoral egos, political interference , limited human resources , differences in standards operating procedures ( SOPs ), and inadequate data sharing . Recommended solutions include regulatory harmonization , SOP alignment , strengthening coordination through regular forums , enhancing professionalism and ethics among law enforcement officials , leveraging digital technology (e-audit, e- prosecution ), and empowering public participation to foster anti - corruption culture . The recovery of state financial losses in corruption cases is a critical component of anti -corruption efforts , highlighting the necessity of ratifying the Draft Law on Asset Confiscation to ensure effective restitution . Comparatively , the United States recovers losses swiftly through litigation and strict regulations ; Singapore experiences minimal losses due to effective prevention and assets seizure ; Malaysia faces significant losses with slow recovery processes ; whereas Indonesia continues to encounter challenges in coordination and regulatory implementation , resulting in suboptimal recovery of state assets